1994
DOI: 10.1007/bf01954488
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal growth and final height in long-term survivors of childhood leukaemia

Abstract: Survival of children with acute lymphoblastic leukaemia (ALL) has increased considerably in recent years and data on the spontaneous growth and final height of these children are conflicting. Therefore, we analysed the longitudinal growth and final height in 52 survivors (33 females, 19 males) of childhood ALL. These children were diagnosed and treated in a single institution, all remained in first remission and were submitted to cranial irradiation with either 2400 or 1800 cGy. None of the patients received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…30,31 In our study, we observed growth retardation du ring treatment mainly among the children who received cranial irradiation. One cause of the growth retardation in patients with ALL is thought to be cranial irradiation, which affects growth hormone secretion, among other results.…”
Section: Height Heightmentioning
confidence: 55%
“…30,31 In our study, we observed growth retardation du ring treatment mainly among the children who received cranial irradiation. One cause of the growth retardation in patients with ALL is thought to be cranial irradiation, which affects growth hormone secretion, among other results.…”
Section: Height Heightmentioning
confidence: 55%
“…Several reports had shown that early puberty in children with ALL might be another factor resulting in reduced final height [5,29,30]. Although in this study pubertal stages, testicular volume or bone age were not routinely documented, pubertal growth spurt and menarche were available for estimation of puberty.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the gender-dependence of effects of irradiation could be related to different age of cerebral development and vulnerability of the nervous structure in boys and girls. According to this, irradiated ALL survivor girls seemed to be particularly affected by precocious puberty and to have experienced greater growth impairment than boys [25,26]. The study conducted by Oeffinger and colleagues achieved similar results, even if they detected an opposite and direct dose-dependent radiotherapy-effect.…”
Section: Introductionmentioning
confidence: 91%